MoWS2 Nanosheet Composite with MXene as Lithium-Sulfur Battery Cathode Material. (25th January 2023) - Feng, Wangjun; Zhao, Zhiqiang; Lei, Ziru; Zhang, Li
Abstract : Due to their superior theoretical specific capacity and energy density, lithium-sulfur (L‒S) batteries are gaining popularity in order to achieve the growing terms for more power generation. However, drawbacks such as low electrical conductivity of the active ingredient sulfur, severe volume expansion and shuttle effect of polysulfides, rapidly decaying battery capacity, and short battery life have hampered their development. A MoWS2 @MXene@CNT composite material is used as the main cathode material for L-S batteries in this study. MoWS2 can improve the electrochemical reaction rate by accelerating polysulfide conversion, whereas MXene can suppress electrode volume expansion. Furthermore, the addition of carbon nanotubes (CNT) with high electrical conductivity improves the rate of the electrochemical reaction. Therefore, the MoWS2 @MXene@CNT composites have good capacity and versatility as cathode materials and enhance the behavior of L-S batteries.